DEVELOPMENT OF A RATIONAL TECHNOLOGY FOR MANUFACTURING WOMEN'S HOLIDAY DRESS IN ETHNO-STYLE USING QR CODES - MARYNCHENKO, INNA (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The article is devoted to the topical issue of combining traditional Ukrainian culture and modern technologies in the field of light industry. The research focuses on the development of an innovative technology for the production of women's holiday dresses in ethnic style, which involves the use of QR codes. The paper analyzes the current state of research in the field of the application of QR codes in clothing production, as well as the features of the Ukrainian ethnic style. Based on the analysis, a dress design was developed that combines traditional Ukrainian ornaments and modern fashion trends. Special attention was paid to the development of a dress manufacturing technology using QR codes. Various options for implementing QR codes in the design of the dress were considered, and algorithms for decoding the information contained in QR codes were developed. It was determined that QR codes on clothing are an innovative way for brands to interact with consumers. By scanning the code, the buyer gains access to additional information about the product: from the brand history to care instructions. This allows you to create a more personalized experience and increase customer loyalty. This tool is especially effective for brands that seek to emphasize their uniqueness and create an emotional connection with the consumer. The article reveals that the process of implementing a new collection is possible by performing the following steps: creating a collection lookbook, showing the collection at fashion weeks, showrooms, pop-up stores, generating traffic on social networks, creating and distributing video content, mobile communications, virtual flash mobs. It is proven that QR codes open up wide opportunities for ethno-fashion brands to create a unique experience for customers. By scanning the code on the embroidery, the buyer can learn the history of the ornament, embroidery master classes, and also get access to exclusive offers. This not only increases the value of the product, but also creates an emotional connection between the brand and the consume. The result of the research is the development of a rational technology for manufacturing women's holiday dresses in ethnic style using QR codes, which allows increasing the competitiveness of the product, attracting a young audience, and popularizing Ukrainian culture.
Keywords: QR codes; ethnic style; women's dress; production technology; Ukrainian culture; innovations